The glycobiome of the rumen bacterium Butyrivibrio proteoclasticus B316(T) highlights adaptation to a polysaccharide-rich environment. - William J Kelly (Public Library of Science (PLoS), 2010)
Determining the role of rumen microbes and their enzymes in plant polysaccharide breakdown is fundamental to understanding digestion and maximising productivity in ruminant animals. Butyrivibrio proteoclasticus B316(T) is a gram-positive, butyrate-forming rumen bacterium with a key role in plant polysaccharide degradation. The 4.4 Mb genome consists of 4 replicons; a chromosome, a chromid and two megaplasmids. The chromid is the smallest reported for all bacteria, and the first identified from the phylum Firmicutes. B316 devotes a large proportion of its genome to the breakdown and reassembly of complex polysaccharides and has a highly developed glycobiome when compared to other sequenced bacteria. The secretion of a range of polysaccharide-degrading enzymes which initiate the breakdown of pectin, starch and xylan, a subtilisin family protease active against plant proteins, and diverse intracellular enzymes to break down oligosaccharides constitute the degradative capability of this organism. A prominent feature of the genome is the presence of multiple gene clusters predicted to be involved in polysaccharide biosynthesis. Metabolic reconstruction reveals the absence of an identifiable gene for enolase, a conserved enzyme of the glycolytic pathway. To our knowledge this is the first report of an organism lacking an enolase. Our analysis of the B316 genome shows how one organism can contribute to the multi-organism complex that rapidly breaks down plant material in the rumen. It can be concluded that B316, and similar organisms with broad polysaccharide-degrading capability, are well suited to being early colonizers and degraders of plant polysaccharides in the rumen environment.